Ground-based measurements of spatial and temporal variability of snow accumulation in East Antarctica - Eisen, Olaf; Frezzotti, Massimo; Genthon, Christophe; Isaksson, Elisabeth; Magand, Olivier; van den Broeke, Michiel R; Dixon, Daniel A; Ekaykin, Alexey; Holmlund, Per; Kameda, Takao; Karlöf, Lars; Kaspari, Susan; et al. (Reviews of Geophysics, 2008)
The East Antarctic Ice Sheet is the largest, highest, coldest, driest, and windiest ice sheet on Earth. Understanding of the surface mass balance (SMB) of Antarctica is necessary to determine the present state of the ice sheet, to make predictions of its potential contribution to sea level rise, and to determine its past history for paleoclimatic reconstructions. However, SMB values are poorly known because of logistic constraints in extreme polar environments, and they represent one of the biggest challenges of Antarctic science. Snow accumulation is the most important parameter for the SMB of ice sheets. SMB varies on a number of scales, from small-scale features (sastrugi) to ice-sheet-scale SMB patterns determined mainly by temperature, elevation, distance from the coast, and wind-driven processes. In situ measurements of SMB are performed at single points by stakes, ultrasonic sounders, snow pits, and firn and ice cores and laterally by continuous measurements using ground-penetrating radar. SMB for large regions can only be achieved practically by using remote sensing and/or numerical climate modeling. However, these techniques rely on ground truthing to improve the resolution and accuracy. The separation of spatial and temporal variations of SMB in transient regimes is necessary for accurate interpretation of ice core records. In this review we provide an overview of the various measurement techniques, related difficulties, and limitations of data interpretation; describe spatial characteristics of East Antarctic SMB and issues related to the spatial and temporal representativity of measurements; and provide recommendations on how to perform in situ measurements.
Keywords: Antarktis; akkumulasjon; fjernmåling; glasiologi; havnivåstigning; innlandsis; paleoklimatologi; snø

Quantarctica, an integrated mapping environment for Antarctica, the Southern Ocean, and sub-Antarctic islands - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; de Pomereu, Jean; Griffiths, Huw; Headland, Robert; Herried, Brad; Katsumata, Katsuro; Le Brocq, Anne; Licht, Kathy; Morgan, Fraser; Neff, Peter D; et al. (Environmental Modelling & Software, 2021)
Quantarctica (https://www.npolar.no/quantarctica) is a geospatial data package, analysis environment, and visualization platform for the Antarctic Continent, Southern Ocean (>40oS), and sub-Antarctic islands. Quantarctica works with the free, cross-platform Geographical Information System (GIS) software QGIS and can run without an Internet connection, making it a viable tool for fieldwork in remote areas. The data package includes basemaps, satellite imagery, terrain models, and scientific data in nine disciplines, including physical and biological sciences, environmental management, and social science. To provide a clear and responsive user experience, cartography and rendering settings are carefully prepared using colour sets that work well for typical data combinations and with consideration of users with common colour vision deficiencies. Metadata included in each dataset provides brief abstracts for non-specialists and references to the original data sources. Thus, Quantarctica provides an integrated environment to view and analyse multiple Antarctic datasets together conveniently and with a low entry barrier.
Keywords: Antarktis; Sørishavet; geografi; kartografi; polarområdene

Short- and long-term variability of the Antarctic and Greenland ice sheets - Hanna, Edward; Topál, Dániel; Box, Jason E.; Buzzard, Sammie; Christie, Frazer D. W.; Hvidberg, Christine; Morlighem, Mathieu; De Santis, Laura; Silvano, Alessandro; Colleoni, Florence; Sasgen, Ingo; Banwell, Alison F.; et al. (Nature Reviews Earth & Environment, 2024)
The variability of the Antarctic and Greenland ice sheets occurs on various timescales and is important for projections of sea level rise; however, there are substantial uncertainties concerning future ice-sheet mass changes. In this Review, we explore the degree to which short-term fluctuations and extreme glaciological events reflect the ice sheets’ long-term evolution and response to ongoing climate change. Short-term (decadal or shorter) variations in atmospheric or oceanic conditions can trigger amplifying feedbacks that increase the sensitivity of ice sheets to climate change. For example, variability in ocean-induced and atmosphere-induced melting can trigger ice thinning, retreat and/or collapse of ice shelves, grounding-line retreat, and ice flow acceleration. The Antarctic Ice Sheet is especially prone to increased melting and ice sheet collapse from warm ocean currents, which could be accentuated with increased climate variability. In Greenland both high and low melt anomalies have been observed since 2012, highlighting the influence of increased interannual climate variability on extreme glaciological events and ice sheet evolution. Failing to adequately account for such variability can result in biased projections of multi-decadal ice mass loss. Therefore, future research should aim to improve climate and ocean observations and models, and develop sophisticated ice sheet models that are directly constrained by observational records and can capture ice dynamical changes across various timescales.
Keywords: Antarktis; glasiologi; innlandsis; klimaendringer; polarområdene

Eight glacial cycles from an Antarctic ice core - Augustin, Laurent; Barbante, Carlo; Barnes, Piers R. F.; Marc Barnola, Jean; Bigler, Matthias; Castellano, Emiliano; Cattani, Olivier; Chappellaz, Jerome; Dahl-Jensen, Dorthe; Delmonte, Barbara; Dreyfus, Gabrielle; Durand, Gael; et al. (Nature, 2004)
The Antarctic Vostok ice core provided compelling evidence of the nature of climate, and of climate feedbacks, over the past 420,000 years. Marine records suggest that the amplitude of climate variability was smaller before that time, but such records are often poorly resolved. Moreover, it is not possible to infer the abundance of greenhouse gases in the atmosphere from marine records. Here we report the recovery of a deep ice core from Dome C, Antarctica, that provides a climate record for the past 740,000 years. For the four most recent glacial cycles, the data agree well with the record from Vostok. The earlier period, between 740,000 and 430,000 years ago, was characterized by less pronounced warmth in interglacial periods in Antarctica, but a higher proportion of each cycle was spent in the warm mode. The transition from glacial to interglacial conditions about 430,000 years ago (Termination V) resembles the transition into the present interglacial period in terms of the magnitude of change in temperatures and greenhouse gases, but there are significant differences in the patterns of change. The interglacial stage following Termination V was exceptionally long—28,000 years compared to, for example, the 12,000 years recorded so far in the present interglacial period. Given the similarities between this earlier warm period and today, our results may imply that without human intervention, a climate similar to the present one would extend well into the future.
Keywords: Antarktis; klimagasser; paleoklimatologi

Future sea level change under CMIP5 and CMIP6 scenarios from the Greenland and Antarctic ice sheets - Payne, Antony J; Nowicki, Sophie; Abe-Ouchi, Ayako; Agosta, Cécile; Alexander, Patrick; Albrecht, Torsten; Asay-Davis, Xylar; Aschwanden, Andy; Barthel, Alice; Bracegirdle, Thomas J; Calov, Reinhard; Chambers, Christopher; et al. (Geophysical Research Letters, 2021)
Projections of the sea level contribution from the Greenland and Antarctic ice sheets rely on atmospheric and oceanic drivers obtained from climate models. The Earth System Models participating in the Coupled Model Intercomparison Project phase 6 (CMIP6) generally project greater future warming compared with the previous CMIP5 effort. Here we use four CMIP6 models and a selection of CMIP5 models to force multiple ice sheet models as part of the Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6). We find that the projected sea level contribution at 2100 from the ice sheet model ensemble under the CMIP6 scenarios falls within the CMIP5 range for the Antarctic ice sheet but is significantly increased for Greenland. Warmer atmosphere in CMIP6 models results in higher Greenland mass loss due to surface melt. For Antarctica, CMIP6 forcing is similar to CMIP5 and mass gain from increased snowfall counteracts increased loss due to ocean warming.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Projected land ice contributions to twenty-first-century sea level rise - Edwards, Tamsin L; Nowicki, Sophie; Marzeion, Ben; Hock, Regine; Goelzer, Heiko; Seroussi, Hélène; Jourdain, Nicolas C; Slater, Donald A; Turner, Fiona E; Smith, Christopher J; McKenna, Christine M; Simon, Erika; et al. (Nature, 2021)
The land ice contribution to global mean sea level rise has not yet been predicted using ice sheet and glacier models for the latest set of socio-economic scenarios, nor using coordinated exploration of uncertainties arising from the various computer models involved. Two recent international projects generated a large suite of projections using multiple models, but primarily used previous-generation scenarios and climate models, and could not fully explore known uncertainties. Here we estimate probability distributions for these projections under the new scenarios using statistical emulation of the ice sheet and glacier models. We find that limiting global warming to 1.5 degrees Celsius would halve the land ice contribution to twenty-first-century sea level rise, relative to current emissions pledges. The median decreases from 25 to 13 centimetres sea level equivalent (SLE) by 2100, with glaciers responsible for half the sea level contribution. The projected Antarctic contribution does not show a clear response to the emissions scenario, owing to uncertainties in the competing processes of increasing ice loss and snowfall accumulation in a warming climate. However, under risk-averse (pessimistic) assumptions, Antarctic ice loss could be five times higher, increasing the median land ice contribution to 42 centimetres SLE under current policies and pledges, with the 95th percentile projection exceeding half a metre even under 1.5 degrees Celsius warming. This would severely limit the possibility of mitigating future coastal flooding. Given this large range (between 13 centimetres SLE using the main projections under 1.5 degrees Celsius warming and 42 centimetres SLE using risk-averse projections under current pledges), adaptation planning for twenty-first-century sea level rise must account for a factor-of-three uncertainty in the land ice contribution until climate policies and the Antarctic response are further constrained.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting